2005
DOI: 10.1086/430318
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of the Effects ofCitrobacter rodentiumInfection in Mice by Pretreatment with Probiotics

Abstract: Pretreatment with probiotics attenuates the effects of C. rodentium infection in mice. Understanding the mechanism of these beneficial effects will aid in determining the efficacy of probiotics in preventing infection with related attaching-effacing enteric pathogens in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…We have previously shown that in vivo use of a probiotic mixture containing L. rhamnosus R0011 and Lactobacillus helveticus R0052 in mice is beneficial in ameliorating intestinal injury in response to C. rodentium (19,20), gastric injury in response to Helicobacter pylori infection (21), and stress-induced barrier dysfunction in epithelial ultrastructure in the colon of stressed rats (48). The response to a nonspecific injury, such as stress, leads to defective mucosal barrier function, enhanced luminal bacterial adherence, and alterations in cellular morphology (40,41 (46) demonstrated that secreted proteins of L. rhamnosus GG prevent tumor necrosis factor alpha-induced apoptosis in human and mouse epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that in vivo use of a probiotic mixture containing L. rhamnosus R0011 and Lactobacillus helveticus R0052 in mice is beneficial in ameliorating intestinal injury in response to C. rodentium (19,20), gastric injury in response to Helicobacter pylori infection (21), and stress-induced barrier dysfunction in epithelial ultrastructure in the colon of stressed rats (48). The response to a nonspecific injury, such as stress, leads to defective mucosal barrier function, enhanced luminal bacterial adherence, and alterations in cellular morphology (40,41 (46) demonstrated that secreted proteins of L. rhamnosus GG prevent tumor necrosis factor alpha-induced apoptosis in human and mouse epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of viable probiotics and their products on pathogen viability. The effects of probiotics on the viability of the pathogen were assessed using coincubation methods, as previously described (20). Briefly, L. rhamnosus GG (10 8 CFU/ml) was coincubated at a ratio of 1:1 (vol/vol) with E. coli O157:H7 (10 7 CFU/ml) in Penassay broth (10 ml) for 3 and 18 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations